2016
DOI: 10.1038/srep32888
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Differentiation of Human iPSCs in a Multicellular Spheroid-based 3D Culture into Hepatocyte-like Cells through Direct Wnt/β-catenin Pathway Inhibition

Abstract: Treatment of acute liver failure by cell transplantation is hindered by a shortage of human hepatocytes. Current protocols for hepatic differentiation of human induced pluripotent stem cells (hiPSCs) result in low yields, cellular heterogeneity, and limited scalability. In the present study, we have developed a novel multicellular spheroid-based hepatic differentiation protocol starting from embryoid bodies of hiPSCs (hiPSC-EBs) for robust mass production of human hepatocyte-like cells (HLCs) using two novel i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 101 publications
2
64
1
Order By: Relevance
“…Also, TGF-β is positively correlated with lower O 2(g) levels and activation of HIF1A during liver organogenesis [31]. In addition, Wnt signaling inhibition is known to control hepatocyte differentiation in 3D culture [32]. The combined inhibition of Wnt and TGF-β significantly increases the expression of albumin (more pronounced by TGF-β inhibition), as opposed of what was observed, when these two pathways were activated (Fig.…”
Section: Discussionmentioning
confidence: 85%
“…Also, TGF-β is positively correlated with lower O 2(g) levels and activation of HIF1A during liver organogenesis [31]. In addition, Wnt signaling inhibition is known to control hepatocyte differentiation in 3D culture [32]. The combined inhibition of Wnt and TGF-β significantly increases the expression of albumin (more pronounced by TGF-β inhibition), as opposed of what was observed, when these two pathways were activated (Fig.…”
Section: Discussionmentioning
confidence: 85%
“…There is a wide variety of solutions to enhance the liver-specific character of the stem cell-derived HLCs. These include chemically defined xeno-free media [47,48], different coating substances and 3D culturing compositions [35][36][37][38][39], as well as co-culturing with supporting cells [26], bioprinting of HLCs onto structures mimicking in vivo situation [49]. It is important to note that the criteria for defining stem cell-derived HLCs were restricted in most cases to the expression of AFP and albumin, secretion of urea and albumin, as well as glycogen storage.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that 3D and so-called sandwich culturing conditions facilitate polarization of hepatocytes and have a positive effect on the hepatic differentiation [35][36][37][38][39]. It has also been reported that bile acids can elevate the expression of liver specific transporters, and enhance their membrane localization [40][41][42].…”
Section: The Effect Of Sandwich Culturing and Tauroursodeoxycholic Acidmentioning
confidence: 99%
“…In the last decades, mounting evidence has indicated that 3D cell culture configuration can lead to phenotypical and functional improvements by providing a permissive context that preserves cellular phenotypes on a molecular and histological level and mimicking the architecture and cell–cell contact of the native tissue. In recent studies, microwell array‐based 3D aggregation methods have been reported to generate multicellular hepatic spheroids . Microwell platforms allow for efficient production of multicellular liver constructs, but cannot create dynamic environment required to maintain viability and functions of large 3D constructs.…”
Section: Resultsmentioning
confidence: 99%